2022
DOI: 10.1177/03000605221141556
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rotational and standard methods of i-gel® insertion in patients of advanced age undergoing general anesthesia: a randomized clinical trial

Abstract: Objective This study was performed to compare the performance of rotational versus standard insertion of the i-gel® (Intersurgical, Wokingham, Berkshire, England) in patients of advanced age. Methods This single-center, randomized, double-blind trial involved 140 patients of advanced age undergoing general anesthesia. The patients were randomized into the standard group and rotational group. The primary objective of this study was to compare the success rate of the first attempt. The secondary outcome indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Previous studies had reported a similarly low rate of blood staining while using I-gel. [ 17 18 ] Keller and Brimacombe[ 19 ] demonstrated that mucosal perfusion progressively decreased with increasing mucosal pressure caused by the inflated cuff of the PLMA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported a similarly low rate of blood staining while using I-gel. [ 17 18 ] Keller and Brimacombe[ 19 ] demonstrated that mucosal perfusion progressively decreased with increasing mucosal pressure caused by the inflated cuff of the PLMA.…”
Section: Discussionmentioning
confidence: 99%